Creativity in Context of Deviant Behavior - Kravtsov, O.G. (Psihologo-pedagogičeskie issledovaniâ, 2019)
In this article author discussing the problem of creativity in context of studying of deviant behavior. The author shows the results of several research of criminal that are underage and normal teenagers creativity abilities. The results of this research appears to be paradoxical, pointing non-linear structure of creativity abilities. By the other words it could be not definitely assert, that low result by creativity tests means low creativity abilities of the respondents with deviant behavior. That is, adolescents with deviant behavior, doing poorly with creativity tests, show very high creative abilities, for example, in the social sphere. According author opinion one of the possible way of overcoming that difficulties is L.S. Vygotsky’s cultural-historical approach. Studying of play activity and imagination development shows, that it is quality differences between deviant and normal persons. The author refers to them object level of development of imagination and stuck on the director's game, low level of imagination and lack of formation of the subject of imagination and play activity. В статье автор рассматривает проблему творчества в контексте изучения девиантного поведения. Приведены результаты нескольких исследований творческих способностей у несовершеннолетних правонарушителей и обычных подростков. По результатам этих исследований был получен довольно парадоксальный результат, указывающий на нелинейную структуру творческих способностей. Иными словами, нельзя однозначно сказать, что низкие показатели по различным тестам креативности говорят о низких творческих способностях у респондентов с девиантным поведением. То есть подростки с девиантным поведением, плохо справляющиеся с тестами креативности, проявляют очень высокие творческие способности, например, в социальной сфере. По мнению автора, одним из возможных путей преодоления этих трудностей является культурно-исторический подход Л.С. Выготского. Изучение развития воображения и игры показало, что есть качественные отличия девиантов от обычных сверстников. К ним автор относит предметный уровень развития воображения и застревание на режиссерской игре, низкий уровень развития воображения и несформированность субъекта воображения и игровой деятельности.